DOMINANCE OF MODULATION AND REDUCTION TECHNIQUES IN THE ARABIC–INDONESIAN SUBTITLE TRANSLATION OF THE FILM NAGA (2023) ON THE NETFLIX PLATFORM - Rizky Umar Hasan; Mokhamad Azis Aji Abdilah; Sujanti; Annisa Ardhiana Eka Putri; Pitri Nutmandani; Fouad Larhzizer (ALLAIS Journal of Arabic Language and Literature, 2026)
Translating Arabic film subtitles into Indonesian presents unique challenges, particularly in bridging linguistic and cultural gaps on global streaming platforms like Netflix. The film Naga (2023) serves as an intriguing subject due to its combination of Saudi Arabian religious-cultural discourse and the horror genre. This study aims to analyze the translation techniques employed in the Indonesian subtitles of the first 30 minutes of the film. This research employs a qualitative descriptive method using document analysis (observation and note-taking) on the subtitle data. The data were analyzed using the translation techniques framework proposed by Molina and Albir (2002). The analysis of 187 dialogue data revealed the application of six translation techniques: modulation, reduction, particularization, adaptation, borrowing, and transposition. Modulation was the most dominant technique (36.4%), followed by reduction (31.6%) and particularization (17.1%). The prominence of modulation and reduction indicates the translator's strong effort to adapt the characters' emotional expressions into the Indonesian cultural context, while simultaneously considering the spatial and temporal constraints (Characters Per Second) of the subtitle screen. These findings affirm that subtitle translation is not merely a linguistic transfer of meaning, but a cultural and contextual negotiation process to ensure the readability and acceptability for the target audience.